Closing the loopholes in becoming better readers / Noli Maishara Hj Nordin, Roslan Sadjirin and Caroline Joseph - Nordin, Noli Maishara; Sadjirin, Roslan; Joseph, Caroline (2013)
Students' comprehension of a text relies much on the strategies exploited during the session. The use of such strategies would enhance students' comprehension of the text, which, in turn helps them in their academic at large. This study aimed to investigate the reading strategies used by English as a Second Language (ESL) low achievers at tertiary level. Particularly, it aimed to identify the reading strategies frequently used by the respective ESL learners. Furthermore, it aimed to find out whether there was any significant different in the type of strategies used by ESL low achievers? Forty undergraduate students were randomly selected as the respondents for this study. A twenty-eight-item questionnaire, which focused on the frequency of use of pre, while, and post-reading strategies was utilised in the study. It was found that ESL low achievers frequently used certain reading strategies to grab the meaning of the text. The ESL low achievers were also reported to significantly use while-reading strategies as their typical remark. The findings suggest that the use of proper reading strategies should be disclosed to students to help them enhance their reading comprehension and make them become effective readers.